Evaluation of the Program for Giving Iron Tablets to Young Women - Rohimah, Yeni Tutu; Astuti, Sri Lestari Dwi; Insiyah, Insiyah; Suyanto, Suyanto (Poltekkes Kemenkes Surakarta, 2023)
Background: Anemia due to iron deficiency is a prevalent health issue that affects many people, particularly women, from early childhood through adulthood. Bleeding can be a problem for pregnant women who have iron deficiency anemia, among other things, during pregnancy, labor, and the puerperium. Low birth weight, early birth, and problems of growth and development that result in stunting are some of the effects that anemic mothers experience while carrying their unborn children. Adolescent anemia continues up until the point at which the adolescent becomes pregnant. To treat iron-deficient anemia, the government is marketing blood replacement tablets. Pupose of study is to determine the effectiveness of iron tablets, the authors worked with the Klaten District Health Office to compare Hb and ferritin levels in pupils who had received blood tablets for 9 months versus kids who had not had blood tablets. Methods: This study used a cross-sectional research approach and is a case analysis study. The SMP Negeri I Jogonalan Klaten is the research location. Study do in June to September 2022. Respondents are 60 pupils from Klaten Public Middle School I, ages 11 to 14, participated in the survey. Of them, 30 female respondents had taken iron supplements for 9 months (40 weeks), while the remaining 30 served as controls and had not received blood supplements. After being told of the advantages of the study, participants who signed a written informed permission form and agreed to take part in it had their ferritin and hemoglobin levels checked. Results: When compared to the control group's ferritin value of 16.13% and Hb value of 6.45%, the treatment group's ferritin value was low (24.14%) and the Hb value was 10.34%. Conclusion: 20% of young women are still found to have anemia. Young women should be prevent anemia.